CORPORATE PERSPECTIVES ON GREEN FINANCE AND ITS INFLUENCE ON FIRM VALUE AND INVESTMENT STRATEGIES IN INDONESIA - Barry, Boubacar Demba; Nurjannah, Dewi; Widagdo, Bambang (Bina Nusantara University, 2025)
This study examines the corporate perspectives on green finance instruments and their impact on firm value and investment strategies among publicly listed companies in Indonesia. While global research on the sustainable finance is extensive, evidence from the emerging economies, particularly using the qualitative approaches, remains limited. Guided by the Resource-Based View (RBV), Signalling Theory, and Stakeholder Theory, the study investigates how corporations frame, justify, and communicate their engagement with green bonds, sukuk, and ESG-linked initiatives. Using a qualitative document analysis approach, data from corporate sustainability reports, annual filings, and regulatory disclosures from 50 companies across multiple sectors between 2021 and 2023 were analysed. The thematic content analysis was applied to identify the patterns in the disclosure narratives and the strategic framing. The findings reveal that green finance instruments serve not only as capital-raising tools but also as strategic resources that improve competitiveness, as market signals that reduce information asymmetry, and as legitimacy mechanisms that reinforce stakeholder trust. The study contributes theoretically by integrating multiple theoretical lenses on green finance adoption and practically by providing suggested ways for regulators, corporate leaders, and investors to enhance disclosure credibility and align ESG strategies with long-term value creation. These insights suggest that robust green finance engagement can become a strategic driver of corporate resilience and stakeholder trust in emerging markets.